Study of the effect of salt concentration on the sensorial qualities of bagoong alamang (shrimp paste), and of some frmentation aspect of the product. - De Los Reyes, Erminia M. (College of Fisheries, University of the Philippines in the Visayas, 1979)
The study was done in two phases. The first phase involved the determination of the most acceptable salt to shrimp ratio for bagoong alamang, while the second phase involved the determination of the changes in amino-N and ammonia-N and the total aerobic and anaerobic count of the product as means for characterizing fermentation of bagoong alamang. For the second phase, the salt to shrimp ratio, which turned out most acceptable, was studied. Among the three salt to shrimp ratios used, such as 1:3, 1:4 and 1:5, the 1:5 sample turned out to be most acceptable. The product had a more appealing color, reddish-purple color and a better flavor. The color of this product, though, was found to deteriorate faster than the other two, as was evidenced by a more rapid intensification of the ammoniacal odor. The second phase of the study revealed no clear pattern or trend for the changes in ammonia-N content of fermented alamang. The amino-N content, on the other hand, showed a maximum value after a 2 days of fermentation, then it decreased considerably on the third day, and increased again slowly thereafter until the 5th day. Microbiological finding revealed the presence of both aerobic and anaerobic halophilic organisms in bagoong alamang. The growth of the anaerobic ones, however, appeared to predominate as fermentation progressed, as was evidenced by a relatively much rapid increase in count. The growth of the aerobic ones increased slowly during the later stages of fermentation, although they showed to be the dominant flora during the initial stages. This trend was observed within a 5-day period of fermenting the product.